Multisensory Processing Can Compensate for Top-Down Attention Deficits in Schizophrenia. (17th July 2021) - Moran, James K; Keil, Julian; Masurovsky, Alexander; Gutwinski, Stefan; Montag, Christiane; Senkowski, Daniel
Abstract: Studies on schizophrenia (SCZ) and aberrant multisensory integration (MSI) show conflicting results, which are potentially confounded by attention deficits in SCZ. To test this, we examined the interplay between MSI and intersensory attention (IA) in healthy controls (HCs) ( N = 27) and in SCZ ( N = 27). Evoked brain potentials to unisensory-visual (V), unisensory-tactile (T), or spatiotemporally aligned bisensory VT stimuli were measured with high-density electroencephalography, while participants attended blockwise to either visual or tactile inputs. Behaviorally, IA effects in SCZ, relative to HC, were diminished for unisensory stimuli, but not for bisensory stimuli. At the neural level, we observed reduced IA effects for bisensory stimuli over mediofrontal scalp regions (230–320 ms) in SCZ. The analysis of MSI, using the additive approach, revealed multiple phases of integration over occipital and frontal scalp regions (240–364 ms), which did not differ between HC and SCZ. Furthermore, IA and MSI effects were both positively related to the behavioral performance in SCZ, indicating that IA and MSI mutually facilitate bisensory stimulus processing. Multisensory processing could facilitate stimulus processing and compensate for top-down attention deficits in SCZ. Differences in attentional demands, which may be differentially compensated by multisensory processing, could account for previous conflicting findings on MSI in SCZ.